Brain Wave Oscillations as an Objective Neurophysiological Biomarker of Homeopathic Subjective Well-Being - Teixeira, Marcus Zulian (Homeopathy, 2024)
Background Homeopathy uses the “similitude principle” to arouse a therapeutic reaction in the body against its own disorders. For this to occur optimally, the medicinal pathogenetic effects must present similarity with the totality of the individual's symptoms. To assess if this similarity has been successfully achieved, Hahnemann states that “improvement in the disposition and mind”—i.e., subjective well-being—is the most important parameter to consider.Aim Our aim was to perform a narrative review of the literature, exploring what is known about subjective well-being as a marker of therapeutic action, and to formulate ways in which subjective well-being might be quantifiable and applied in future homeopathy research.Results The concept of subjective well-being has been extensively studied in the complementary and conventional medical literature. Improved well-being has been observed in clinical trials, including those in the fields of positive psychology and meditation. Positive subjective outcomes of this nature are supported by objective evidence through associated changes in brain oscillatory activity using electroencephalography and/or “brain mapping” by functional magnetic resonance imaging. Neurophysiological responses in the brain have been identified in subjects after they ingested a homeopathic medicine.Conclusions The concept of subjective well-being is supported by a body of literature and is a measurable entity. When viewed from the perspective of electrophysiological changes, brain activity is an objective neurophysiological biomarker with a potential to quantify individual well-being in the context of homeopathy research.
Keywords: homeopathy; subjective well-being; positive psychology; meditation; brain mapping; EEG; drug individualization